HINDRANCES TO MALE INVOLVEMENT IN MATERNAL HEALTH CARE IN KWALI AREA COUNCIL, ABUJA, NIGERIA (2014)
Involving men in Maternal Health Care (MHC) has become important because of the realization that men’s behaviour can significantly affect health outcomes of women and children. Male involvement in MHC is generally poor in many developing countries including Nigeria. Reasons for poor male involvement in MHC services have not been adequately documented. This study was therefore designed to determine hindrances to male involvement in MHC in Kwali Area Council, Abuja, Nigeria. A community-based cross-sectional study was conducted among 370 candidates recruited from households in Kwali Area Council, Abuja using a four-stage sampling technique: Kwali Area Council from the 6 Area Councils of the FCT, wards selection, settlements selection and selection of respondents. A pre-tested interviewer administered questionnaire containing information on knowledge of MHC was assessed using a 23-point scale. Scores of < 15 and >15 were categorized as low and high knowledge respectively. Levels of male involvement was assessed using a 6-point scale with scores of < 4 and > 4 were categorised low and high involvement respectively. Three Focus Group Discussions (FGDs) were also conducted among men in 3 randomly selected wards out of the 10 wards in the Area Councils. The FGDs were tape recorded, transcribed and subjected to content analysis. The quantitative data were analysed using descriptive statistics and Chi-square test at 0.5% level of significance. Mean age of the respondents was 37.9 ± 9.5 years, educational status: no formal education (33.2%), Islamic education (21.1%), primary education (15.9%), OND/NCE (14.1%), HND/B.Sc (8.1%) and secondary education (7.6%). Respondents Religion: Christians (58.1%), Muslims (41.4%) and traditionalist (0.5%). Ethnical composition: Gbagi (78.1%), Ibo (6.2%), Hausa (3.2%), Yoruba (2.7%) and other tribes (9.8%). Marital Status: currently married (99.2%) with (15.9%) were in polygamous marriage. Most (84.3%) had heard of MHC services with health workers (25.8%) being the leading source of information among respondents. Many (68.9%) and (31.1%) of respondents had poor and good knowledge of MHC respectively. Witchcraft (45.7%) and family planning methods (46.9%) were perceived to be the causes of maternal mortality. Mean knowledge score of respondents who had ever and never heard of MHC were 14.5±3.5 and 11.6±3.0 respectively. Only 42.0% of men had high level of involvement in MHC. Perceived hindrances to male involvement in MHC included poor knowledge of maternal health care (95.1%), negative health workers’ attitude (83.4%), financial constraints (95.7%) among others. The FGD participants perceived MHC as care given to women from pregnancy till delivery. Maternal Health Care was perceived as women affairs accounting for the low male involvement. Significantly more of secondary school holders and above (50.5%) had good knowledge of maternal health care than other educational qualifications (p<0.05) Poor knowledge, societal norms, negative Health workers’ attitude, financial constraints among others constitute the main factors which militate against male involvement in maternal health care services. Community health education programme which focuses on reorientation on gender roles will improve knowledge of men on maternal health care issues. Continuing education training programme should be organized for health workers on attitudinal change to clients.